Tupiperla tessellata (Brauer, 1866) (Plecoptera: Gripopterygidae): description of the nymph with morphological and distributional notes. - Lecci, Lucas Silveira; Sarmento, Felipe Ribeiro Pereira; Bispo, Pitgoras DA Conceio [UNESP] (Magnolia Press, 2025)
Specimens of Tupiperla tessellata (Brauer, 1866) were collected in Serra do Japi, located in the Atlantic Forest of southeastern Brazil, including pre-emergent nymphs. These nymphs were reared to adulthood, enabling the association between the two life stages. Based on this association, the nymphs of T. tessellata were identified and described. Additionally, we provide photographs of the holotype, update the species distribution, and offer taxonomic notes on the species. This represents the first documented nymphal association for a nominal species of Tupiperla, which comprises 26 described species.